Paved stone steps going down from Walkeshwar Temple to Banganga Tank - Banganga by Ghosh, Ayan (2023)
Paved stone steps going down from Walkeshwar Temple to Banganga Tank. In the past, most temples along the parikrama were connected to the ghats which allowed pilgrims to directly enter the temple after performing purification rituals in the tank. Unfortunately, access to the tank is now blocked at several points due to encroachments on the ghats.